Estimation of the structural parameters of carbon using the X-ray diffractometers with different angular resolutions. (November 2015) - Fujimoto, Hiroyuki
Abstract : The structural parameters of coke and mesocarbon microbeads were measured using three diffractometers with different angular resolutions based on the standard X-ray diffraction measurement procedure for carbon (Gakushin method). There was no observable difference in the values of the lattice constants, a 0 and c 0, obtained using the three instruments. However, because the half width of the profile is affected by the angular resolution there were differences in the measured crystallite size. TANSO 2015 (No. 267), 113–117.